Pyrenean tourism confronted with sustainable development: partial and hesitant integration - Sylvie Clarimont; Vincent Vlès (Revue de Géographie Alpine)
The cross-border comparative study of the forms and outcomes of the introduction of sustainable tourism by inter-communal efforts in the western Pyrenees has revealed the difficulties of imposing the model, and, worse, this model is often the alibi justifying a mass of incoherent tourist policy, which, being defective in forward planning and territorial coherence, makes it difficult to apply. Research on this theme was carried out from 2004-2006 at the Université de Pau et des Pays de l'Adour in collaboration with the University of Saragosse. The three conclusions it reached are presented in summarized form as follows: 1 - incorporation of tourism in the field of sustainable development has been belated and hesitant, resulting in big delays as far as its application is concerned; 2 - in France more than in Spain, the multi-level nature of inter-communal bodies together with the lack of transfer of competences in mass tourism have produced the breaking-up of territorial-based development and its management, excluding long-term consideration project-wise. 3 - the overbearing presence of big leisure-construction operations is upturning the traditional residential and land management balance and reveals insufficient initial planning efforts.